2013
DOI: 10.1093/jxb/eru225
|View full text |Cite
|
Sign up to set email alerts
|

Scratching the surface: genetic regulation of cuticle assembly in fleshy fruit

Abstract: The hydrophobic cuticular membrane of land plants performs a number of important roles during fruit development, including protection from a range of abiotic and biotic stresses. The components of the fleshy fruit cuticle are synthesized and secreted from the epidermal cells. While the biosynthetic and transport pathways of the cuticle have been thoroughly investigated for a number of decades, the regulatory mechanisms allowing fine tuning of cuticle deposition are only now beginning to be elucidated. Transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
62
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 117 publications
1
62
0
Order By: Relevance
“…Tomato represents an excellent model for studying cuticle formation in fleshy fruits as well as more broadly in plant taxa (Hen-Avivi et al, 2014;Martin and Rose, 2014;Fich et al, 2016). Studies of tomato cuticles span many different fields, ranging from the analysis of cuticle composition and architecture (Mintz-Oron et al, 2008;Buda et al, 2009;Yeats et al, 2012a;Philippe et al, 2016;Segado et al, 2016), biosynthetic pathways, assembly and regulation (Shi et al, 2013;Lashbrooke et al, 2015), interaction with other metabolic pathways and developmental processes (Kosma et al, 2010;Giménez et al, 2015), mechanical properties (Schreiber, 2010;España et al, 2014), as well as the significance of the cuticle for agronomically important traits such as fruit glossiness, postharvest shelf-life, fruit cracking, and resistance to pathogens Shi et al, 2013;Buxdorf et al, 2014;Petit et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Tomato represents an excellent model for studying cuticle formation in fleshy fruits as well as more broadly in plant taxa (Hen-Avivi et al, 2014;Martin and Rose, 2014;Fich et al, 2016). Studies of tomato cuticles span many different fields, ranging from the analysis of cuticle composition and architecture (Mintz-Oron et al, 2008;Buda et al, 2009;Yeats et al, 2012a;Philippe et al, 2016;Segado et al, 2016), biosynthetic pathways, assembly and regulation (Shi et al, 2013;Lashbrooke et al, 2015), interaction with other metabolic pathways and developmental processes (Kosma et al, 2010;Giménez et al, 2015), mechanical properties (Schreiber, 2010;España et al, 2014), as well as the significance of the cuticle for agronomically important traits such as fruit glossiness, postharvest shelf-life, fruit cracking, and resistance to pathogens Shi et al, 2013;Buxdorf et al, 2014;Petit et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The differentially expressed TFs included those with a possible link to the circadian clock, with two genes (Solyc01g095030 and Solyc10g084370) encoding MYB-related TFs of the REVEILLE family (Farinas and Mas, 2011), one of which was expressed at lower levels in gpat6-a, and six genes encoding CONSTANS-like TFs (Valverde, 2011), one of which (Solyc12g005660) was expressed at much lower levels. Despite the large number of differentially expressed TFs identified, the group did not include TFs that have been reported to regulate cuticle formation in tomato or other species (Shi et al, 2013;Borisjuk et al, 2014;Hen-Avivi et al, 2014), other than a MIXTA-like MYB TF (Oshima and Mitsuda, 2013), whose role in tomato was described recently (Lashbrooke et al, 2015). We observed that the expression of SlMIXTA-like (Solyc02g088190) was lower in the gpat6-a mutant than in the wild type (Supplemental Table S5).…”
Section: The Gpat6-a Mutant Has Abnormal Fruit Cuticle Thickness Andmentioning
confidence: 96%
See 2 more Smart Citations
“…Finally, the cuticle is increasingly shown to be important in development (Koornneef et al, 1989;Yeats and Rose, 2013) and pathogenesis (Lee and Dean, 1994;Gilbert et al, 1996;Bessire et al, 2007;Delventhal et al, 2014). It is therefore unsurprising that interest in cuticle composition, structure, and physiology is increasing (Buschhaus et al, 2014;Hen-Avivi et al, 2014;HerediaGuerrero et al, 2014;Xu et al, 2014). Moreover, a greater understanding of the relationship between structure and chemical composition of cuticle waxes is vital for enhancing agriculture yields, as it will further our knowledge of how plants regulate water balance and inform the application of nutrition (foliar feeds) and pesticides, leading to improved formulation strategies for agrochemicals.…”
mentioning
confidence: 99%